A nomogram prediction of postoperative surgical site infections in patients with perihilar cholangiocarcinoma. Issue 25 (June 2017) - Li, Long; Ding, Jie; Han, Jun; Wu, Hong
Abstract : Abstract: Surgical site infection (SSI) is one of the major morbidities after radical resection for perihilar cholangiocarcinoma (PHCC). This study aimed to clarify the risk factors and construct a nomogram to predict SSIs in patients with PHCC. A total of 335 consecutive patients who underwent hepatectomy combined with hepaticojejunostomy between January 2013 and December 2015 were analyzed retrospectively. SSIs, including incisional (superficial and deep) and space/organ infection, were defined according to the Centers for Disease Control and Prevention (CDC)'s National Nosocomial Infection Surveillance (NNIS) system. Risk factors associated with postoperative SSIs were analyzed by univariate and multivariate analyses. A nomogram was developed on the basis of results from the multivariate logistic model and the discriminatory ability of the model was analyzed. PHCC patients had higher organ/space SSI rate than incisional SSI rate after radical resection. Multivariate analysis showed that risk factors indicating postoperative overall SSIs (incisional and organ/space) included coexisting cholangiolithiasis [odds ratio (OR): 6.77; 95% confidence interval (95% CI): 2.40–19.11; P  < .001], blood loss >1500 mL (OR: 4.77; 95% CI: 1.45–15.65; P   =  .010), having abdominal surgical history (OR: 5.85; 95% CI: 1.91–17.97; P   =  .002), and bile leakage (OR: 15.28; 95% CI: 5.90–39.62; P  < .001). The β coefficients from the multivariate logistic model were used to construct the model for estimation of SSI risk. The scoring model was as follows: −4.12 +1.91 × (coexisting cholangiolithiasis  =  1) + 1.77 × (having previous abdominal surgical history  =  1) +1.56 × (blood loss >1500 mL  =  1) + 2.73 × (bile leakage  =  1). The discriminatory ability of the model was good and the area under the receiver operating characteristic (ROC) curve (AUC) was 0.851. In PHCC patients, there may be a relationship between postoperative SSIs and abdominal surgical history, coexisting cholangiolithiasis, bile leakage, and blood loss. The nomogram can be used to estimate the risk of postoperative SSIs in patients with PHCC.